Periodontitis and Systemic Diseases: A Review - Saxena, Vrinda; Dayma, Ashwini (Journal of Orofacial Research, 2017)
Periodontitis is one of the inflammatory-infectious diseases of the oral cavity, which results in an alteration in the production of host inflammatory mediators. Oral cavity has plentiful diverse bacteria that can spread different sites of the body particularly in immune compromised individuals and results in various systemic diseases. As the oral cavity is the mirror image of our systemic health, hence maintenance of oral health is equally important. This paper reviews the etiology of periodontitis and systemic relation.